Acting like god?: ways to embody the divine in religious play and deity possession - Hauser, Beatrix (Diskus, 2008)
This paper explores the aesthetics of divine embodiments in eastern India by taking a close look at the mimetic faculty of the human body in two types of cultural performances. I shall compare (1) the mode of acting as a deity on the Ramlila stage, i.e., during a religious play that is enacted to produce sacred reality rather than merely representing Rama or other gods; and (2) the expressiveness of women who, as part of a procession, embody a goddess and thus may become possessed by her. Whereas in both types of events performers refer to divine agency in order to rationalize their behaviour, they impersonate the deity in substantially different ways, particularly with respect to the display of emotions. Unlike several scholars who argue that in ritual drama the process of acting is likely to evoke an experiential state classified as possession, I suggest that we need to differentiate mimetic forms to understand better both deity possession and Indian theatre. Whereas the possessed body develops an expressiveness of its own, the concept of līlā does not subscribe to the ideal of aesthetic realism.